Nationwide analysis of COVID-19 complications, outcomes, and costs of childbirth in Spain - Álvarez-del Río, Blanca; Sánchez-de Prada, Laura; Arroyo-Hernantes, Irene; Álvarez, F. Javier; Tamayo, Eduardo; Gutiérrez-Abejón, Eduardo (Frontiers in Medicine, 2025)
IntroductionPregnant women are considered a vulnerable group for COVID-19 with an increased risk for complications. The objective of this study is to describe in-hospital mortality, pregnancy outcomes, and direct hospital costs associated with COVID-19 in women at the time of childbirth.MethodsThis retrospective nationwide population-based registry study collects data on complications, outcomes, and direct hospital costs from women hospitalized for childbirth, recorded in the Minimum Basic Data Set obtained from the National Surveillance System for Hospital Data in Spain between 2020–2022. Hospitalization characteristics, complications related to pregnancy and childbirth, outcomes, and hospitalization costs are compared between COVID-19-positive and non-COVID-19 women at the time of childbirth.ResultsA total of 779,387 women were admitted between 2020 and 2022 with a record of childbirth in Spanish hospitals. Of these, 15,792 (2.06%) had COVID-19 at the time of delivery. These women had a longer length of stay (3.53 days), higher rates of intensive care unit (ICU) admission (2.53%), ventilation/intubation (0.91%), and in-hospital mortality (0.06%) (p < 0.0001). This group also exhibited higher rates of spontaneous premature onset of labor (7%) and postpartum hemorrhage (3.45%), as well as a higher rate of labor induction (6.27%) (p < 0.001). Additionally, a higher single stillbirth rate (0.73%) was found among COVID-19-positive women (p = 0.0002). A significant higher risk of postpartum hemorrhage (OR = 1.14), embolism (OR = 7.98), acute respiratory distress syndrome (OR = 35.5), temporary tracheostomy (OR = 4.89), ventilation/intubation (OR = 6.85), and single stillbirth (OR = 1.32) was found in COVID-19 women (p < 0.05). The mean cost per patient was €4,066.48, 25.06% higher than that for non-COVID-19 women (p < 0.0001). Stratification by age showed an increasing trend in costs with age, reaching €6,492.12 in women ≥45 years old, where the ICU admission rate reached 8.09%.ConclusionThese findings show that COVID-19 at the time of childbirth occurs in 2 out of every 100 cases and increases the risk of complications related to pregnancy and childbirth, as well as mortality and hospitalization costs. These data are related to SARS-CoV-2 variants circulating from 2020–2022, and current variants could give different risks. Our evaluation should be useful for health authorities to allocate resources and professionals to implement preventive measures, such as vaccination and screening, due to the increased morbidity, mortality and costs in this group.